2016
DOI: 10.1177/1478929915623968
|View full text |Cite
|
Sign up to set email alerts
|

The Rise and Fall of Social Capital: Requiem for a Theory?

Abstract: We distinguish between social capital theory and social capital political discourse in order to reflect upon their relation with one another and neoliberalism. We claim this analytical distinction is useful to understand the existence of a feedback effect between theory and political discourse. During the 1990s, the connection between social capital theory and neoliberalism has been transposed from academia to political discourse, thus contributing to popularise social capital within the public sphere. Over ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 53 publications
0
32
0
2
Order By: Relevance
“…The analyses reported here have identified a very substantial shift away from welfare and towards workfare that the Thatcher governments tried to initiate, which began to take effect under John Major but was achieved—and sustained—by the New Labour administrations of Blair and Brown and has not since been undermined by Conservative austerity, strongly anti-welfare policies that have been masked by the political rhetoric of social cohesion (cf. Ferragina and Arrigoni 2016). Society has converged on anti-welfare attitudes, reducing the spatial divide that has long characterised Great Britain and substantially altering the contest between the political parties.…”
Section: Discussionmentioning
confidence: 97%
“…The analyses reported here have identified a very substantial shift away from welfare and towards workfare that the Thatcher governments tried to initiate, which began to take effect under John Major but was achieved—and sustained—by the New Labour administrations of Blair and Brown and has not since been undermined by Conservative austerity, strongly anti-welfare policies that have been masked by the political rhetoric of social cohesion (cf. Ferragina and Arrigoni 2016). Society has converged on anti-welfare attitudes, reducing the spatial divide that has long characterised Great Britain and substantially altering the contest between the political parties.…”
Section: Discussionmentioning
confidence: 97%
“…Above we have seen how social capital has been increasingly colonized by financial capital as neoliberalism has incrementally gained its control over economic and political system along with the rising financialization. According to social scientists Emanuele Ferragina and Alessandro Arrigoni, rising economic inequalities exacerbated by the 2008 financial crisis have demonstrated that "the neoliberal political agenda is incompatible with the aim to generate social capital" (Ferragina and Arrigoni 2017). By examining the critical case of Britain, they come to a conclusion that "social capital theory (at least Putnam's version) can no longer obscure the fact that the neoliberal political agenda has acted as a brake upon civic participation" (Ferragina and Arrigoni 2017, p. 363).…”
Section: The Proliferation Of Immoral Credit and The Quest For An Ethmentioning
confidence: 99%
“…It is fair to say that this notion, predicated on the idea that many would volunteer, fell by the wayside and became something of a political embarrassment to the Conservative Party (Woodhouse 2015). Ferragina and Arrigoni (2016) comment that in an age of economic crisis such as that precipitated by the 2008 financial crash, "the policy aim to bolster social capital is incompatible with a neo-liberalist political agenda" (p. 355). Neoliberalism as a political credo sits firmly within the Conservative canon for reducing the welfare state and promoting the predominance of the private sector over the public.…”
Section: Political and Policy Changesmentioning
confidence: 99%